Lack of expression of the VHS107 gene family in the lipopolysaccharide- sensitive B cell subset of X-linked immunodeficiency-defective mice (The Rockefeller University Press, 1986)
The expression of the VH T15 gene product was analyzed in the sera and in the supernatants of polyclonally activated B cells of X-linked immunodeficient (xid) mice. We found that defective males, contrary to normal females, do not express the VH T15 gene product even on antibodies devoid of anti-PC specificity. RNA analysis of polyclonally activated cells with VH specific probes revealed that xid-defective B cells do not express the entire S107 or part of the J606 VH family. Members of the J558 family, on the other hand, are equally well expressed among defective males and normal female B cells. These results strongly suggest that VH families are asymmetrically represented among B cell subsets.